Infection and colonisation in V-V ECMO—not a predictor of poor outcome - Fisser, Christoph; Malfertheiner, Maximilian Valentin (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
In patients suffering from most sever acute respiratory failure the use of veno-venous extracorporeal membrane oxygenation (V-V ECMO) has become a widely accepted treatment option. Despite improvements in patient management and technical devices mortality in adult patients receiving V-V ECMO is still high (1). Beside the underlying disease accountable for the need of V-V ECMO, treatment complications of the therapy add to morbidity and mortality. The most frequent complications associated with V-V ECMO treatment are bleeding, thrombosis and infections (2,3).